Peran Komunitas Pecinta Sejarah (Kompas) dalam Mendukung Kegiatan Pembelajaran Sejarah - erika puspadewi; Murdiyah Winarti (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The title of this research is “The Role of Historical Community (KOMPAS) in Supporting History Learning (a Descriptive Study of an Extracurricular KOMPAS at SMAN 22 Bandung.”The researcher’s background takes the theme of the research based on an interest in extracurricular activities in field of historical study at Senior High School. The choice of the Historical Community as the object of research is because this community the only extracullicullar based on historical learning that exist in Bandung and has not yet received attention among academics. The main problem in this research is “What is the role of the historical community (KOMPAS) in supporting students historical learning at school?”  Based on these problems, the writer divides them into three problem formulations. How was the development of the Historical Community (KOMPAS) in 2015-2019? How has the Historical Community (KOMPAS) designed its programs to support history learning? What is the impact of the Historical Community (KOMPAS) on learning history in 2015-2019?.The method used in this research is descriptive study. The results of this study indicate that the background to the establishment of the Historical Community (KOMPAS) is the development of a history study group that is engaged in developing students' historical insight and skills. After the Historical Community (KOMPAS) was officially established as an extracurricular, this group attempted to create interactive history learning programs that support history learning. The impact of theHistorical Community at SMAN 22 Bandung is to provide a variety of learning resources in developing history learning materials.